HUBUNGAN ANTARA KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMK NEGERI 3 PADANG - Sari, Yuliana; R., Syahrul; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACTThis article was written to describe the relationship of listening skill of observation report texts to the skill of writing the text of the result of observation of the seventh grade students of SMK Negeri 3 Padang. This research is a quantitative research with descriptive method. The sample in this study amounted to 30 people. The data of this research is score of skill test result listening the observation report text. Based on data analysis and discussion, the following three things are obtained. First, the skill of writing the text of the result of observation of the seventh grade students of SMK Negeri 3 Padang is in good qualification (65,56). Second, the skill of listeningto the text of the result of observation of the seventh grade students of SMK Negeri 3 Padang is in good qualification (79,44).Kata kunci: hubungan, menyimak, menulis, teks laporan hasil observasi